(3TQM JgPjH GdefWb hGdcdGe ddJaJRGfjs - (3GdjROj, YHO Gddg Hf GdMSjf Hf YHO Gddg, J (B1015 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bhdg GdMeO ddg GaJJM HMeO Gddg HYO GdHSedI GJHGYG HNjQ GdcdGe hGbJOGA HMOjK NjQ GdCfGe Ydjg hBdg hGdUdGI hGdSdGe aEf bdJ MOjK GdGHJOGA eQhj aj cd ef GdJSejI hGdJMejO s
(3BNQgG (B:s
(3hbjd gPG ETGQI Edi GdYde hchfg CTHg HGdebUO XGgQ Hd GdebUhO eYfi GdYde GdYed LYd Gddg hEjGce ef GdQGSNjf aj GdCeQjfs
(3aj Ghdg fbhd HGdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 80s
(3eYLe GdeDdajf (B2 / 239s
(3cTa GdXfhf (B1 / 516s
(3GdPQjYI (B13 / 161s
Keywords: (3GdadSaI hGdefWbs